ANALISIS PENDAPATAN PEDAGANG BUAH DI KOTA MAKASSAR (Universitas Patria Artha, 2019)
The existence of the informal sector in the city is caused by the inability of the formal sector to accommodate or provide employment for all job seekers. One of the informal sectors that is interesting to study is street vendors, because of its ability to create jobs and provide cheap goods and services as well as a safety valve that can prevent widespread unemployment and social unrest. Therefore this study aims to determine the income of street vendors, especially fruit traders on the roadside in the city of Makassar. Data was collected through interviews and direct observation with selected respondents, then analysis using income analysis and break-even analysis. The results showed that the fruit traders in the city of Makassar on average gained enough profits to meet the needs of their family's life, although it was found that there were some fruit fields that suffered losses, but the losses they suffered were still far below the level of wages they got.